ANALISIS HUKUM ISLAM DAN HUKUM POSITIF TERHADAP PEREMPUAN YANG MENIKAH DALAM MASA IDDAH - Zaenal Arifin; Amelia Fadilah (SAMAWA, 2025)
Marriage in the iddah period is a complex legal issue in Islamic fiqh and national marriage regulations in Indonesia.This research uses a literature study method with a qualitative normative-descriptive approach that analyzes shar'i arguments, scholarly opinions, and national legal regulations related to iddah.The results show that in Islamic law, marriage in the iddah period is invalid and can have serious consequences such as nasab disputes, uncertainty about the status of children, and violations of sharia principles. On the national legal side, regulations such as the KHI and the Marriage Law have adopted the principles of iddah, but have not provided explicit sanctions for violations. The phenomenon of flash marriages and siri marriages during the iddah period is still common due to weak public understanding, lack of administrative supervision, and economic pressures. The difference between classical fiqh and positive law in determining the beginning of the iddah period also has the potential to cause conflicts of interpretation. These findings emphasize the need for regulative reform and contextual Islamic law education as well as strengthening digital administrative systems in marriage institutions. This study concludes that the successful implementation of the iddah period as a legal and moral institution depends on the harmony between fiqh norms and positive law, as well as the synergy between public education and bureaucratic modernization to maintain the integrity of Islamic family law in Indonesia. Keywords: Islamic and Positive Law, Marriage, Women in Iddah Period.